2020
DOI: 10.1097/j.pain.0000000000001876
|View full text |Cite
|
Sign up to set email alerts
|

Placebo hypoalgesia: racial differences

Abstract: No large-cohort studies that examine potential racial effects on placebo hypoalgesic effects exist. To fill this void, we studied placebo effects in healthy and chronic pain participants self-identified as either African American/black (AA/black) or white. We enrolled 372 study participants, 186 with a diagnosis of temporomandibular disorder (TMD) and 186 race-, sex-, and age-matched healthy participants to participate in a placebo experiment. Using a well-established paradigm of classical conditioning with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…Of the 23 studies included (Table 1), nine studies used the Diagnostic Criteria for TMD (DC/TMD) to diagnose TMDm 25–34 10,35–47 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 studies included (Table 1), nine studies used the Diagnostic Criteria for TMD (DC/TMD) to diagnose TMDm 25–34 10,35–47 .…”
Section: Resultsmentioning
confidence: 99%
“…Alongside the promise of QST in improving the characterization of pain, and in turn, the prescription of individualized treatment interventions, limitations of this methodology must also be addressed. As highlighted in our descriptions of QST in TMD and placebo research, sex and racial effects regarding pain sensitivity, and racial effects regarding placebo efficiency have been observed, and thus need be accounted for when analyzing results ( 57 , 58 ). In addition, effects of age must be considered when incorporating QST, as loss of sensory function has been observed in older adults for cold, warmth, mechanical, and vibratory detection thresholds ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we assessed thermal heat pain threshold and thermal heat pain tolerance in TMD participants as a proxy for the QST procedure. We found that Afro-American Blacks had lower pain tolerance in both TMD participants and healthy control participants ( 57 ). Additionally, we found women in the TMD cohort to have lower levels of both thermal heat pain threshold and thermal heat pain tolerance than men ( 58 ).…”
Section: Temporomandibular Disordersmentioning
confidence: 95%
See 2 more Smart Citations